Oral health status among the under five children attending at OPD of Dhaka Dental College Hospital (Update Dental College Journal, 2016)
Aim: The purpose of the study was to assess the oral health status among the under five children. Study revealed to find out selected dental conditions like dental caries, gingival and periodontal conditions and DMFT score and socio-demographic background.Methods: A descriptive type of cross sectional study was conducted at Dhaka Dental College Hospital at children OPD.A total 120 under five childrens parents were interviewed through a structured questionnaire followed by oral examination through a checklist.Results: Among 120 children, 44.17% were male and 55.83% were female. Most of the children (94.17%) were found to clean teeth regularly by themselves. 70.83% children clean their teeth themselves with brush and paste once daily spending 1-3 minutes. Maximum children (73.33%) clean their teeth before breakfast. Fluoridated toothpaste was being used by most of the children (85.84%). Only 4.17% child change their toothbrush every month and 55.83% every two months and 40% after 3-6 months. Regarding feeding history, it was found that 58.33% children were given exclusive breast feeding. Most of the children (63.33%) take soft drinks. It was found from the study that 87.50% children had pink color oral mucosa and their gingival condition was normal. Though prevalence of dental caries was 96.67% but overall oral hygiene status was good (86.67%).Conclusion: The study revealed that, dental caries among the under five children was a major health concern creating awareness among the people about their own and their childrens oral health through appropriate plan can reduce the dental diseases. Moreover mass media and general education of the people create vital role in this regards.Update Dent. Coll. j: 2015; 5 (2): 09-17